Development of Nanomaterials to Target Articular Cartilage for Osteoarthritis Therapy - Rao, Chenyu; Shi, Sirong (Frontiers in Molecular Biosciences, 2022)
Osteoarthritis (OA) is an obstinate, degradative, and complicated disease that has drawn much attention to the public around the world. Characterized by its stubborn symptoms and various sequela, OA causes much financial burden on both patients and the health system. What’s more, conventional systematic therapy isn’t effective enough and causes multiple side effects. There’s much evidence that nanoparticles have unique properties, including high penetration, biostability, and large specific surface area. Thus, it’s urgent to exploit novel medication to OA. Recently, nanomaterials have been sufficiently studied, controlling diverse nano-drug delivery systems (DDSs) and targeted nano therapeutical molecules. The nanomaterials are primarily intra-articular injected under the advantages of high topic concentration and low dosage. After administration, the DDS and targeted nano therapeutical molecules can specifically react with the components, including cartilage and synovium of a joint in OA, attenuating the chondrocyte apoptosis, matrix degradation, and macrophage recruitment to alleviate arthritis. The DDSs could load with conventional anti-inflammatory drugs, antibodies, RNA, etc., targeting chondrocytes, synovium, or extracellular matrix (ECM) and releasing the molecules sequentially. The targeted nano therapeutical molecules could directly get to the targeted tissue, alleviating the inflammation and promoting healing. This review will comprehensively collect and evaluate the targeted nanomaterials to articular cartilage in OA.